A pH-triggered delayed-release chronotherapeutic drug delivery system of aceclofenac for effective management of early morning symptoms of rheumatoid arthritis. (17th November 2015) - Sanka, Krishna; Pragada, Rajeswara Rao; Veerareddy, Prabhakar Reddy
Abstract: Context : Rheumatoid arthritis (RA) is differentiated as an early morning exacerbation of the core arthritis condition associated with increase in pain and stiffness in joints and necessitate for medication. Objective : The aim of the present work was to develop and optimise a pH-triggered delayed-release colon-specific aceclofenac microspheres and to accomplish chronotherapy of RA. Methods : A 3-factor, 3-level Box–Behnken design (BBD) was used to optimise selected variables. Developed formulation was evaluated for in vivo delayed response and anti-arthritis activity in rats. Results : The particle size and encapsulation efficacy of these microspheres were 117.36 ± 10.54 µm and 85.06 ± 5.85%, respectively. Optimised formulation was analysed by SEM, DSC, X-RPD and FTIR. The in vivo evaluation reveled delayed anti-inflammatory activity in carrageenan-induced rats and anti-arthritic activity in freund's adjuvant-induced arthritis rats. Conclusion : The optimised aceclofenac microspheres formulation is potential for the chronotherapy of early morning symptoms of RA.